The Influence Computer Assisted Auditing Tools and Techniques (CAATTs) and Professional Ethics on Auditor Performance - Rutmada Silalahi; Panubut Simorangkir; Taufiq Akbar (Yayasan Ilomata, 2022)
This study was conducted with the aim of analyzing the effect of the application of computer-assisted audit technique systems and professional ethics on auditor performance. The data used in this study are the results of processing questionnaire data given to auditors who work in public accounting firms in the Jakarta area. The method used in this research is a purposive sampling method with a total of 92 respondents. Testing the analysis using SPSS 25 by testing the validity, reliability, multiple linear regression, classical assumption test, and hypothesis testing. The results of this study indicate that the application of a computer-assisted audit technique system has a positive and significant effect on employee performance with a significance level of 0.000 <0.05 and professional ethics has a positive and significant effect on employee performance with a significance level of 0.000 <0.05. The results also show that the application of a computer-assisted audit technique system and professional ethics have a joint or simultaneous effect on auditor performance with a significance level of 0.000 < 0.05.